Monte Carlo simulation of radio frequency plasmas in O2 - Settaouti, L.; Settaouti, A. (2008)
Summary: The use of radio frequency (RF) driven discharges in many fields, including material processing, microelectronics and aerospace industry, necessitates development of effective numerical predictive tools to understand and design their behaviour. The structure of RF discharges in O2 is examined for the electrons, positive and negative ions, where electron-neutral collisions and ion-neutral collisions are taken into consideration. Some detailed properties of radio frequency plasmas are presented using Monte Carlo simulation. The simulation results show that most of the RF external electric field is absorbed in the sheath regions. Whereas electrons respond easily to the oscillating RF electric field, ions cannot oscillate with the RF electric field. The oscillations of the electron cloud determine the instantaneous sheath thickness near each electrode. The mean energy and the density of charged particles are also discussed, and the effects of gas pressure on discharge parameters are studied
Simboli u naslovu
Bibliografija: 43 jed
Sažetak
Keywords: Fizika plazme -- Mjerenje -- Metode; Fizika plazme -- Kompjutorska simulacija; Monte Carlo metoda -- Primjena